MENELAAH KRITERIA DESAIN INDUSTRI SET/SEPERANGKAT DALAM PERMOHONAN PELINDUNGAN DESAIN INDUSTRI DI INDONESIA - Wiliayu; Sangayu Ketut Laksemi Nilotama; Achmad Syarief (Universitas Trisakti, 2023)
To protect Industrial Designs owned in Indonesia from being copied by other parties, the public submits applications for Industrial Designs through the office of the Directorate General of Intellectual Property (DJKI). Industrial Design Applications consist of 2 (two) types, namely one Industrial Design and one set of Industrial Designs. However, there are still many people who do not understand the criteria for a set of Industrial Design. To help the public determine the type of Industrial Design, a criterion for Industrial Design is formulated from the applicable legal regulations in Indonesia. This study uses a qualitative descriptive approach by collecting and identifying data originating from empirical cases, namely the application for a set of Industrial Design registered at the DJKI office with the set of Industrial Design rules that apply in Indonesia as well as evaluation of the actual conditions of several experts through interview sessions. From the identification and interview results, 4 (four) set of Industrial Design criteria were obtained which could be useful in helping the applicant understand how the set of Industrial Design criteria apply in Indonesia. Keywords: criteria, industrial design set/set, industrial design protection Untuk melindungi Desain Industri yang dimiliki di Indonesia agar tidak ditiru oleh pihak lain, masyarakat mengajukan permohonan Desain Industri melalui kantor Direktorat Jenderal Kekayaan Intelektual (DJKI). Permohonan Desain Industri terdiri dari 2 (dua) jenis yaitu satu Desain Industri dan Desain Industri set/seperangkat. Namun masih banyak masyarakat yang belum memahami kriteria Desain Industri set/seperangkat. Untuk membantu masyarakat menentukan jenis Desain Industri maka dirumuskan suatu kriteria Desain Industri dari aturan hukum yang berlaku di Indonesia. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan mengumpulkan dan mengidentifikasi data yang berasal dari kasus empirik yaitu permohonan Desain Industri set/seperangkat yang tercatat pada kantor DJKI dengan aturan Desain Industri set/seperangkat yang berlaku di Indonesia serta evaluasi kondisi aktual dari beberapa pakar melalui sesi wawancara. Dari hasil identifikasi dan wawancara diperoleh 4 (empat) kriteria Desain Industri set/seperangkat yang dapat bermanfaat membantu pemohon memahami bagaimana kriteria Desain Industri set/seperangkat yang berlaku di Indonesia.Kata kunci: kriteria, desain industri set/seperangkat, pelindungan desain industri